(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Medical laboratory science plays a crucial role in the healthcare system, providing essential diagnostic information that guides patient care and treatment decisions. This comprehensive review explores the diverse aspects of the medical laboratory science profession, including the scope of practice, educational requirements, technological advancements, and future challenges. The increasing complexity of diagnostic testing, coupled with the growing demand for personalized medicine, necessitates a highly skilled and adaptable medical laboratory workforce. Additionally, the integration of emerging technologies, such as automation, molecular diagnostics, and data analytics, is transforming the practice of medical laboratory science. As the healthcare landscape continues to evolve, it is imperative to recognize the vital contributions of medical laboratory professionals and to foster an environment that supports their ongoing professional development and growth. This review aims to provide a comprehensive understanding of the current state and future directions of medical laboratory science, emphasizing the critical role of these professionals in delivering high-quality, patient-centered care.